Propofol Inhibits Ischemia/Reperfusion-Induced Cardiotoxicity Through the Protein Kinase C/Nuclear Factor Erythroid 2-Related Factor Pathway - Li, Shengqiang; Lei, Zhen; Zhao, Meng; Hou, Yonghao; Wang, Di; Xu, Xingli; Lin, Xiaowen; Li, Jingxin; Tang, Shuhai; Yu, Jingui; Meng, Tao (Frontiers in Pharmacology, 2021)
Both hydrogen peroxide (H2O2, H) and ischemia/reperfusion (IR) can damage cardiomyocytes, which was inhibited by propofol (P). The present research was designed to examine whether propofol can reduce myocardial IR injury by activating protein kinase C (PKC) / nuclear factor erythroid-2-related factor 2 (NRF2) pathway in H9C2 cells and rat Langendorff models. H9C2 cells were assigned to four groups (N=3): Control, H, H+P, H+P+chelerythrine (CHE). Morphology and NRF2 were evaluated. 24 rats were assigned to four groups (N=6): Control, IR, IR+P, IR+P+CHE. The level of lactate dehydrogenase (LDH), superoxide dismutase (SOD), and creatine kinase-MB (CK-MB) in perfusion fluid and NRF2, HO-1, and PKC in myocardial tissue were assessed. The morphology of cardiomyocytes and NRF2 localization were also evaluated. After 24 h, H2O2 increased H9C2 cell mortality. IR, which increased LDH and CK-MB expression and reduced SOD expression, boosted the pathological damage and infarcts of myocardial tissue after reperfusion. However, propofol inhibited all these effects, an activity that was antagonized by chelerythrine (CHE). Both H2O2 and IR slightly induced nuclear translocation of NRF2 and HO-1 expression, which was significantly promoted by propofol. SiRNA knockout of PKC inhibited propofol-induced NRF2 nuclear location and HO-1 expression, which was promoted by the PKC agonist phorbol 12-myristate 13-acetate (PMA). The results suggest that propofol pretreatment provides protection against IR injury by activating of PKC / NRF2 pathway